Analisis Literasi Digital (ICT) Peserta Didik Melalui Pemanfaatan Web Kahoot dalam Pembelajaran Koloid - Jumila Jumila; Maria Paristiowati; Zulhipri Zulhipri; Edith Allanas (LPPM Universitas Negeri Jakarta, 2018)
This study aims to determine the digital literacy of students after learning process on colloidal topic using the Kahoot web. The study was conducted at SMA Negeri 22 Jakarta, Indonesia in 2017/2018 school year using qualitative research methods. Web Kahoot is used as an evaluation tool in the learning process on colloidal topic. Data collection techniques through observation, interviews, reflective journals, and dissemination of questionnaires for needs analysis and digital literacy. The dimensions of digital literacy analyzed in this study consist of information, communication, content-creation, safety and problem-solving. The results of this study show that students have a good category in the dimensions of information, communication, content-creation, and problem-solving, while the safety dimensions are categorized very well. Based on the results of the research, Kahoot web can foster students’ digital literacy in the learning process of colloidal topic. Keywords: Digital Literacy, Web Kahoot, Colloid